Epidemiological investigation on diseases of Larimichthys crocea in Ningbo culture area - Xu, Shengwei; Ge, Mingfeng; Feng, Juan; Wei, Xinxian; Tan, Honglian; Liang, Zheng; Tong, Guixiang (Frontiers in Cellular and Infection Microbiology, 2024)
Introduction Due to the high-density farming of Larimichthys crocea over the years, diseases caused by pathogens such as bacteria, viruses, and parasites frequently occur in Ningbo, posing a huge threat and challenge to the sustainable and healthy development of the L. crocea’s bay farming industry. In order to understand the diseases occurrence in L. crocea farming in Ningbo area, an epidemiological investigation of L. crocea diseases was carried out through regular sampling in 2023. Methods From April to October 2023, routine sampling of L. crocea was conducted monthly in various farming areas in Ningbo. Each time, live or dying L. crocea with obvious clinical symptoms were sampled, with a total number of 55 L. crocea collected. The samples were preserved in ice bags and transported to the laboratory for pathogen detection(including bacterial isolation and identification,virus identification, and parasites detection). Results A total of fifty-five fish dying L. crocea with obvious clinical symptoms were collected in this study, of which 78.18% (43/55) were detected with symptoms caused by pathogenic infection, while 21.82% (12/55) did not have identified pathogens, which were presumed to be breeding abrasions, nutritional metabolic disorders, unconventional pathogens infection or other reasons. A total of twenty-five pathogenic bacteria strains were isolated, which mainly were Pseudomonas plecoglossicida and Vibrio harveyi, accounting for 52% (13/25) and 32% (8/25) of the pathogenic bacteria strains, respectively. Among them, both V. harveyi and Streptococcus. iniae co-infected one fish. Additionally, three other bacterial strains including Nocardia seriolae, Staphylococcus Saprophyticus, and Photobacterium damselae subsp.damselae were isolated. Microscopic examination mainly observed two parasites, Cryptocaryon irritans and Neobenedenia girellae. In virus detection, the red sea bream iridovirus (RSIV) was mainly detected in L. crocea. Statistical analysis showed that among the fish with detected pathogens, 55.81% (24/43) had bacterial infections, 37.21% (16/43) had parasitic infections, and 37.21% (16/43) had RSIV infections. Among them, five fish had mixed infections of bacteria and parasites, three had mixed infections of bacteria and viruses, three had mixed infections of parasites and viruses, and one L. crocea had mixed infections of viruses, bacteria, and parasites. Discussion These findings indicate that these three major types of diseases are very common in the L. crocea farming area in Ningbo, implying the complexity of mixed infections of multiple diseases.